Busemann-Petty Problems for Quasi Lp Intersection Bodies. (31st October 2017) - Zhou, Yanping; Wu, Shanhe
Abstract : We investigate the L p dual geominimal surface area and volume forms of Busemann-Petty problems for the quasi L p intersection bodies and establish some new geometric inequalities. Our results provide a significant complement to the researches on Busemann-Petty problems for intersection bodies.